The institutional logics perspective : a new approach to culture, structure and process / Patricia H. Thornton, William Ocasio, Michael Lounsbury. - Thornton, Patricia H.; Ocasio, William; Lounsbury, Michael (Oxford University Press, 2012)
This work analyses, synthesises, and develops theoretical and methodological tools in the rising new school in institutional analysis, the institutional logics perspective, which offers opportunities to examine how individual and organisational actors are a product of multiple social locations in an inter-institutional system.